pH-sensitive supramolecular self-assembled peptide hydrogel for the treatment of esophageal cancer - Ye, Gaobing; Luo, Shiyao; Zafar, Hajra; Ge, Honglei; Liu, Binbin; Wang, Nan; Jin, Yu; Wang, Miao; Chen, Xu; Ye, Xiaoming (Frontiers in Pharmacology, 2024)
Esophageal cancer is one of the most common cancers in the world, ranking sixth in cancer-related mortality. Doxorubicin (DOX), as a classic broad-spectrum, non-specific small-molecular anti-tumor drug, has achieved widespread use, including in the treatment of esophageal cancer. However, due to its strong cardiotoxicity, poor tumor-targeting ability, and short half-life, the clinical application of DOX has been greatly limited. In this research, we designed and successfully synthesized a peptide sequence IEIIIK (IEK for short) with excellent pH responsiveness. Under physiological conditions (pH 7.4), the peptide can encapsulate DOX and self-assemble into a stable hydrogel (DOX-IEK) through hydrophobic and electrostatic interactions. After being injected into the acidic tumor microenvironment, the protonation degree of alkaline amino acid lysine increased and the negative charge of glutamate decreased, directly leading to enhanced electrostatic repulsion and subsequent hydrogel dissociation. Released DOX can accumulate in tumor tissue and achieve anti-tumor efficacy. More importantly, the hydrogel can act as a drug reservoir for sustained drug release, improving the drug targeting ability, prolonging the duration of drug administration to compensate for the short half-life of DOX, and reducing systemic toxicity. Ideal anti-tumor efficacy has been achieved in both the in vitro and in vivo experiments.